Computed virtual chromoendoscopy versus standard colonoscopy with targeted indigocarmine chromoscopy: a randomised multicentre trial. Issue 1 (6th October 2008) - Pohl, J; Lotterer, E; Balzer, C; Sackmann, M; Schmidt, K-D; Gossner, L; Schaab, C; Frieling, T; Medve, M; Mayer, G; Nguyen-Tat, M; Ell, C
Abstract : Objective: Colonoscopy is the accepted gold standard for screening of neoplastic colorectal lesions, but the substantial miss rate remains a challenge. Computed virtual chromoendoscopy with the Fujinon intelligent colour enhancement (FICE) system is a new dyeless imaging technique that might allow higher rates of adenoma detection. Methods: This is a prospective randomised five tertiary care centre trial of colonoscopy in the FICE mode versus standard colonoscopy with targeted indigocarmine chromoscopy (control group) in consecutive patients attending for routine colonoscopy. Histopathology of detected lesions was confirmed by evaluation of endoscopic resection or biopsy specimens. Results: 871 patients were enrolled, and 764 patients (344 female, mean age 64 years) were subjected to final analysis (368 in the FICE group, 396 in the control group). In total, 236 adenomas (mean of 0.64 per case) were detected in the FICE group and 271 adenomas (mean of 0.68 per case) in the control group (p = 0.92). There was no statistically significant difference in the percentage of patients with ⩾1 adenoma between the control group (35.4%) and the FICE group (35.6%) (p = 1.0). For the differential diagnosis of adenomas and non-neoplastic polyps, the sensitivity of FICE (92.7%) was comparable with that of indigocarmine (90.4%) (p = 0.44). Conclusions: At colonoscopy, adenoma detection rates are not improved by virtual chromoendoscopy with the FICE system compared with white light endoscopy with targeted indigocarmine spraying. However, FICE can effectively substitute for chromoscopy concerning the differentiation of neoplastic and non-neoplastic lesions.